Diabetic nephropathy: the role of inflammation in fibroblast activation and kidney fibrosis - Kanasaki, Keizo; Taduri, Gangadhar; Koya, Daisuke (Frontiers in Endocrinology, 2013)
Kidney disease associated with diabetes mellitus is a major health problem worldwide. Although established therapeutic strategies, such as appropriate blood glucose control, blood pressure control with renin-angiotensin system blockade and lipid lowering with statins, are used to treat diabetes, the contribution of diabetic end-stage kidney disease to the total number of cases requiring hemodialysis has increased tremendously in the past two decades. Once renal function starts declining, it can result in a higher frequency of renal and extra-renal events, including cardiovascular events. Therefore, slowing renal function decline is one of the main areas of focus in diabetic nephropathy research, and novel strategies are urgently needed to prevent diabetic kidney disease progression. Regardless of the type of injury and etiology, kidney fibrosis is the commonly the final outcome of progressive kidney diseases, and it results in significant destruction of normal kidney structure and accompanying functional deterioration. Kidney fibrosis is caused by prolonged injury and dysregulation of the normal wound-healing process in association with excess extracellular matrix deposition. Kidney fibroblasts play an important role in the fibrotic process, but the origin of the fibroblasts remains elusive. In addition to the activation of residential fibroblasts, other important sources of fibroblasts have been proposed, such as pericytes, fibrocytes and fibroblasts originating from epithelial and endothelial mesenchymal transition. Inflammatory cells and cytokines play a vital role In the process of fibroblast activation. In this review, we will analyze the contribution of inflammation to the process of tissue fibrosis, the type of fibroblast activation and the therapeutic strategies targeting the inflammatory pathways in an effort to slow the progression of diabetic kidney disease.